JUSTIFICATION OF STRUCTURAL-INFORNATIONAL CONNECTIVITY INDICATOR WHEN ANALYZING RELIABILITY OF TELECOMMUNICATION SYSTEMS AND NETWORKS - Kalekina, T. G.; Kovalenko, T. N. (Radio Electronics, Computer Science, Control, 2010)
In this work the integrated reliability indicators for telecommunication systems and networks are proposed, that consider both structural and functional network characteristics. The indicators make it possible to evaluate not only potential reliability of a telecommunication network which is the upper bound of structural reliability but also network reliability subject to limited channel throughput.